2016
DOI: 10.1002/lpor.201600079
|View full text |Cite
|
Sign up to set email alerts
|

In situ measurement of the effective nonlinear absorption order in multiphoton photoresists

Abstract: Knowledge of the order of the effective nonlinear absorption in multiphoton photoresists is a key element in the development of improved materials for multiphoton absorption polymerization (MAP). The direct measurement of this nonlinearity has proven challenging. A new technique called 2‐beam initiation threshold (2‐BIT) is presented that allows for the unambiguous, in situ measurement of the order of the effective nonlinear absorption using a simple optical arrangement that can be employed with virtually any … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 21 publications
2
29
1
Order By: Relevance
“…The processes so far only differ on repetition rate and pulse duration assuming that the laser power is adjustable. Other groups 3739 have shown that a variation of these two parameters is possible for two-photon polymerization. These results suggest that the repetition rate and pulse duration is adaptable for the polymerization of microneedles towards equal parameters for both laser processes.…”
Section: Resultsmentioning
confidence: 99%
“…The processes so far only differ on repetition rate and pulse duration assuming that the laser power is adjustable. Other groups 3739 have shown that a variation of these two parameters is possible for two-photon polymerization. These results suggest that the repetition rate and pulse duration is adaptable for the polymerization of microneedles towards equal parameters for both laser processes.…”
Section: Resultsmentioning
confidence: 99%
“…Another approach for measuring the order of effective nonlinear absorption in photoresists is the two‐beam initiation threshold (2‐BIT) technique . This technique involves combining two interleaved pulse trains to expose the photoresist.…”
Section: Indirect Methodsmentioning
confidence: 99%
“…The insets show the absorption spectra of these photoinitiators in methanol, with the effective wavelengths for two‐photon and three‐photon absorption indicated as dashed and dashed‐dotted lines, respectively. (Reproduced with permission . Copyright 2106, Wiley)…”
Section: Indirect Methodsmentioning
confidence: 99%
“…A different method to measure the order of nonlinear absorption was described by Fourkas and coworkers in a technique they named the two-beam initiation threshold (2-BIT) technique [ 23 ]. This method involves splitting an ultrafast laser into two pulse trains, beam #1 and beam #2, and then recombining the pulses with a delay so as to double the repetition rate of the laser.…”
Section: Nonlinearity Ordermentioning
confidence: 99%
“…The insets show the UV-vis absorption spectra and the wavelength equivalent of two- or three- photon absorption by the 800 nm excitation laser. Reproduced from [ 23 ].…”
Section: Figurementioning
confidence: 99%